(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
For the spatio-temporal analysis of the active vegetation period climatic parameters variability, a meteorological data array from 6 meteorological stations for the last 20-year period was processed using statistical-analytical and comparative methods. The study is showed an increase in the active vegetation period in 2 days at the Yalutorovsk Station to 7 days at the Pudino Station, when comparing two ten-year periods (2005–2014 and 2015–2024). The average long-term date shift for these stations was 6 days in Spring and 4 days in Autumn. An increase in the sum of active temperatures in the second ten-year period with a maximum increase at the Tomsk Station of +266℃ was noted.